A New Technique for Jaw Thrust in Unconscious Craniofacial Trauma Patients - Verma, Gaurav (International Journal of Dental Research, 2013)
The loss of consciousness is one of the commonly encountered emergency situations in maxillofacial trauma patients. Apart from benign syncope, there are other causes for unconsciousness. Majority of these patients have intact respiratory muscle activity, but the airway patency is compromised due to airway obstruction by tongue fall back. Traditionally head tilt-chin lift and jaw thrust techniques were employed to maintain patency of the airway. Head tilt-chin lift technique involves tilting the head backward and thus is dangerous in case of suspected cervical spine injury in trauma cases. Jaw thrust is an efficient method and can be performed in cervical spine injury cases. But it requires continuous forward pull on mandible till the time patient regains consciousness; which is physically strenuous for rescuer. The purpose of this article is to present a new technique for jaw thrust which is based on similar principle of traditional jaw thrust. The advantage is that, jaw thrust can be maintained for an extended time period in these patients.